The Zinshaus market and gentrification dynamics: The transformation of the historic housing stock in Vienna, 2007–2019. (April 2022) - Musil, Robert; Brand, Florian; Huemer, Hannes; Wonaschütz, Maximilian
This article intends to contribute to the debate on the quantification of gentrification, which is constrained by two main obstacles: firstly, the operationalisation of displacement of socially weak households, which appears as an elusive phenomenon. Secondly, the consideration of the specific urban context, in particular the regulation of the housing market. Based on a case study for Vienna, this paper introduces a new empirical approach, which does not focus on households, but on the tenement conversion of the historic housing stock. Here, the transformation as legal conversion and demolition of historic tenement houses (German: Zinshäuser ) serve as an alternative indicator for the operationalisation and quantification of displacement processes. The empirical analysis of Zinshaus transformations observed for 2007-2019 for the first time provides an estimation of gentrification dynamics in Vienna. Results point to a pronounced cyclicality in transformation dynamics. Hence, spatial cluster and hotspot analyses reveal a strong concentration of Zinshaus transformations and a clear shift from central bourgeois to peripheral working-class neighbourhoods. Further, a multilinear regression model confirms the impact of Zinshaus transformations on the social dynamics in these neighbourhoods. However, data do not indicate a social shift triggered by upper-class households, but by new migrant groups and well-educated middle-class households. Beyond the case of Vienna, this analysis underlines the relevance of quantitative gentrification approaches based on housing-market segments and their conversion. It proposes applying the Zinshaus as an indicator to make the variety of the urban context visible.